2017
DOI: 10.1021/acschembio.7b00046
|View full text |Cite
|
Sign up to set email alerts
|

Phanerochaete chrysosporium Multienzyme Catabolic System for in Vivo Modification of Synthetic Lignin to Succinic Acid

Abstract: Whole cells of the basidiomycete fungus Phanerochaete chrysosporium (ATCC 20696) were applied to induce the biomodification of lignin in an in vivo system. Our results indicated that P. chrysosporium has a catabolic system that induces characteristic biomodifications of synthetic lignin through a series of redox reactions, leading not only to the degradation of lignin but also to its polymerization. The reducing agents ascorbic acid and α-tocopherol were used to stabilize the free radicals generated from the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…These results provide insight into the complex extra- and intracellular enzyme systems of P. chrysosporium (ATCC 20696). Based on this complex enzyme pool, P. chrysosporium has an excellent catabolic ability to convert aromatics to acid compounds, which supports the biodegradation mechanism of lignin by P. chrysosporium suggested in our previous study ( 8 ).…”
Section: Genome Announcementsupporting
confidence: 86%
See 1 more Smart Citation
“…These results provide insight into the complex extra- and intracellular enzyme systems of P. chrysosporium (ATCC 20696). Based on this complex enzyme pool, P. chrysosporium has an excellent catabolic ability to convert aromatics to acid compounds, which supports the biodegradation mechanism of lignin by P. chrysosporium suggested in our previous study ( 8 ).…”
Section: Genome Announcementsupporting
confidence: 86%
“…Our previous study found that P. chrysosporium (ATCC 20696) degraded monolignols and synthetic lignin to succinic acid ( 8 ). This finding suggested that P. chrysosporium (ATCC 20696) catalyzed not only reactions involving side chains of lignin compounds, but also ring cleavage, indicating that this fungus uses a unique catabolic system in lignin modification.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Phanerochaete chrysosporium is a decomposer in carbon cycle (such as lignin degradation) [40]. These results suggested that the composition of microbial networks had varied considerably in the RNI soils when compared with the NS soils.…”
Section: Taxonomic Diversity Of Rhizosphere Microbiota and Network Stmentioning
confidence: 87%
“…Among them, Rhizophagus irregularis, an arbuscular mycorrhizal fungi, can improve phosphorus uptake and water use efficiency in plants [92]. Phanerochaete chrysosporium is a decomposer in carbon cycle [93]. Macrophomina phaseolina produced macrolide [94].…”
Section: Discussionmentioning
confidence: 99%